RNAi-chitosan biopesticides for managing forest insect pests: an outlook - Mogilicherla, Kanakachari; Roy, Amit (Frontiers in Forests and Global Change, 2023)
The expanding world population demands superior forest protection to fulfil feasible environmental certainty. The persistent pest infestations negatively influence forest health and cause substantial economic losses. In contrast, the traditional use of conventional pesticides results in a loss of soil microbial biodiversity, a drop in the population of pollinators, and adverse effects on other non-target organisms, including humans. Global forestry is looking for solutions to reduce the adverse environmental effects of current chemical pesticides. RNAi-nanotechnology has recently drawn much attention for its use in pest management. The advantages of engineered RNAi-chitosan nano-formulations in terms of simple digestion and dissolution, non-toxicity, high adsorption power, potential biodegradation in nature, and widespread availability and costeffectiveness, have been well documented for pest management in agroecosystems. However, deploying such control strategies in forest ecosystems is still pending and demands further research.Hence, we highlight the putative uses of RNAi-chitosan biopesticides and their preparation, characterization, and putative application methods for forest pest management. We also discussed potential environmental risks and plausible mitigation strategies.